Protection as a Human Fundamental Need: Re-Conceiving Signs of Safety for Social Work in the Republic of Ireland - Flynn, Susan (My University, 2021)
Large scale reform of statutory child protective services in the Republic of Ireland is underway, prompted by adoption of the national strengths-based and safety-organised practice approach, known as ‘Signs of Safety.’ Despite the radical change it impels, critical commentary from the academy on the conventions of Signs of Safety remains conspicuous by its absence. One reading of Bronfenbrenner’s (1979) seminal ecological systems approach is that to appreciate implications of Signs of Safety for children and families at risk, we must surpass a sequestered concern with child protection and welfare alone. To substantiate this, and embed a reconceived Signs of Safety, Max Neef et al.’s (1986, 1989, 1991) human scale development theory is critically deployed through an augmented, rather than exclusive focus, on the axis of protection needs within the typology of fundamental human needs. To aid this, critical application of theory is partially reworked and appropriated through a life course perspective, to better account for life span positioning. Overall, the sustaining proposition of the paper, is that academic interrogation of Signs of Safety is both a practical and ethical imperative, and a necessary complement to large scale organisational change underway.
PUBLISHED
Keywords: Child protection; Ireland; Life-course; Signs of Safety